Lei 10.639/2003 e o ensino de geografia na educação básica: contribuições a partir dos Catopés em Montes Claros, MG - Fagundes, Márcia Verssiane Gusmão (2016)
This work is the result of a survey conducted in the city of Montes Claros, located in the north of Minas Gerais. It aims to understand the Law 10.639 / 2003 and its use in teaching geography. To achieve the context and cover the different aspects that this law reaches, the proposed work has initially passed by understanding the legislation dealing with the specific issue. Delimited to the Constitution of 1988 as a starting point, then the laws that emanated from this higher law were analyzed. Among them, the Law 9.394 / 96, which constitutes the guidelines and bases of national education and specifies the approach to the contributions of different cultures and ethnic groups in the official curriculum of the Network of Brazil's education. With the Federal Law 10.639 / 2003, there was the obligatory theme "History and Afro-Brazilian culture. To know how it was going the application of Law 10.639 / 2003 in Geography Teaching were interviewed four geography teachers who worked in two public schools in Montes Claros. Beside the contributions that the interviewed teachers brought to the subject of research, proposals are also presented for Teaching Geography using as a basis the Law 10639/2003, the Common basic Curriculum of Minas Gerais, and the Curriculum Proposal of the Municipal System of Montes Claros Education.